Russian and foreign students’ involvement in the educational process in the context of the digital distance educational technologies use in the Russian universities - M. A. Tanina; V. V. Bondarenko; V. A. Yudina; O. A. Zyablikova (Вестник университета)
In the context of global changes in the world socio-economic system, the formation of an international educational research space, in the technological platform of the education system, the widespread use of distance learning technologies it is extremely relevant to conduct a comparative analysis of the involvement of Russian and foreign students in the educational process in Russian universities. The article provides the results of an electronic questionnaire survey of 760 foreign and 2,280 Russian students at universities located in 38 regions of the Russian Federation in all federal districts. Russian and foreign students assessed their level of involvement in the educational process in distance and face-to-face learning according to the parameters of four types of involvement: emotional (affective), behavioral, cognitive and academic. Involvement in the educational process during the distance learning decreases among all students, while for foreign students it is to a greater extent than for Russian students, which is due to the linguistic, cultural, mental characteristics of this category of students. Organizational, technical, psychological and emotional barriers were identified as problems that reduce the involvement in the educational process in the distance learning format of Russian and foreign students.